Analisis Strategi Resiliensi UMKM Tempe Khas Ngrayun Ponorogo - Riska Diah Pratami; Fery Setiawan (The Academy Of Management and Business, 2022)
Micro, Small and Medium Enterprises (MSMEs) are one of the sectors that have an important role in the regional economy, including in Ponorogo. This is because most of the population has low education and lives in Micro, Small and Medium Enterprises, both in the traditional and modern sectors. This study aims to examine the strategy of survival and development of Ngrayun tempe products which are one of the typical products of the Ngrayun Ponorogo District. This study uses primary data with data collection techniques used in this study are interviews and observations, to determine the cause of the product still survives until now. This study uses a descriptive analysis method, which is to identify the factors that cause MSME Typical Ngrayun Tempe products to survive which are then formulated in the MSME strategy model. The population is Tempe Khas Ngrayun entrepreneurs who are in Ngrayun Village, Ngrayun District. The sampling technique used purposive sampling technique with 6 business actors. The results of the study were a model of survival strategy and the development of MSMEs for typical Tempe Ngrayun products. Based on data analysis, information was obtained that the factors causing survival were the level of product demand was still high, product durability was short, and the taste of the product was maintained. Meanwhile, the development strategy is to try to maintain traditional processing methods in the midst of the widespread use of chemicals and technological advances.